A practical guide to renewable energy : microgeneration systems a nd their installation - kitcher, chris (London ; New York : Routledge, 2012)
"Learn more about renewable energy, how to install and inspect renew able energy systems and gain certification. This is a perfect introduct ion to one of the construction industry's leading growth areas. It prov ides an overview of all types of renewable energy sources, as well as i nformation relating to the installation and inspection of renewable ene rgy systems. The practical focus in this book will give you the confide nce to pass micro-generation exams, discuss the subject with clients an d work on all new and emerging renewable energy systems. It does this b y providing you with: Step-by-step instructions in how to fit and test renewable energy systems Clear diagrams, photos and flow charts that de monstrate core principles Questions and answers that enable you to test your knowledge and further your understanding of the subject As a stud ent or professional this textbook will provide the information needed t o pass your course and is also an ideal onsite reference. Chris Kitcher is an Electrical Installation lecturer at Central Sussex College, auth or of the bestselling Practical Guide to Inspection, Testing and Certif ication of Electrical Installations and has 45 years of experience in t he electrical industry"--
Includes index.
Keywords: Electric power systems; Renewable energy sources